A Precious-Metal-Free Hybrid Electrolyzer for Alcohol Oxidation Coupled to CO2-to-Syngas Conversion - Bajada,MA; Roy,S; Warnan,J; Abdiaziz,K; Wagner,A; Roessler,MM; Reisner,E (Angewandte Chemie, 2020)
© 2020 The Authors. Published by Wiley-VCH Verlag GmbH & Co. KGaA Electrolyzers combining CO2 reduction (CO2R) with organic substrate oxidation can produce fuel and chemical feedstocks with a relatively low energy requirement when compared to systems that source electrons from water oxidation. Here, we report an anodic hybrid assembly based on a (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) electrocatalyst modified with a silatrane-anchor (STEMPO), which is covalently immobilized on a mesoporous indium tin oxide (mesoITO) scaffold for efficient alcohol oxidation (AlcOx). This molecular anode was subsequently combined with a cathode consisting of a polymeric cobalt phthalocyanine on carbon nanotubes to construct a hybrid, precious-metal-free coupled AlcOx–CO2R electrolyzer. After three-hour electrolysis, glycerol is selectively oxidized to glyceraldehyde with a turnover number (TON) of ≈1000 and Faradaic efficiency (FE) of 83 %. The cathode generated a stoichiometric amount of syngas with a CO:H2 ratio of 1.25±0.25 and an overall cobalt-based TON of 894 with a FE of 82 %. This prototype device inspires the design and implementation of nonconventional strategies for coupling CO2R to less energy demanding, and value-added, oxidative chemistry.